AkarjayaMotor: The All-in-One Motorcycle Platform - Mohd Irwan, Khairin Irfan; Saringat, Mohd Zainuri (Applied Information Technology And Computer Science, 2026)
This project aims to develop a comprehensive e-commerce platform for Akarjaya Motor Sdn Bhd, a leading motorcycle dealership in Parit Raja, Batu Pahat. The platform will support motorcycle sales, service bookings, and online payments, enhancing operational efficiency and customer convenience. Currently, Akarjaya Motor faces challenges due to its reliance on face-to-face transactions and lack of digital presence. To address this, the project adopts the Prototyping Model, enabling iterative development based on stakeholder feedback to ensure the system meets user needs. Key processes include requirement gathering, rapid prototyping, and continuous refinement. The final system will serve as the central hub for business operations, offering secure payment integration, a user-friendly interface, efficient service management, and role-based account features for administrators and customers. The platform is expected to significantly improve customer satisfaction and digital competitiveness, positioning Akarjaya Motor for future growth and strengthening its role as a key player in the motorcycle industry.